HUBUNGAN STATUS GIZI DENGAN KEJADIAN ANEMIA PADA SANTRIWATI DI PONDOK PESANTREN DARUL ULUM PETERONGAN JOMBANG - Is Rinieng Nur Sya`Bani; Sri Sumarmi (Jurnal Keperawatan Muhammadiyah, 2016)
Objective: to analyzed the relationship between nutritional status and anemia among female students.  Methods: A cross sectional study was done at Muzamzamah-Chosyiah dormitory, islamic boarding school Darul Ulum in Jombang district east java. Sample size of 106 female students who aged 12-15 years old,  was drown from population of 175 female students, Hemoglobin level was measured by using hemoglobin meter, body weight was measured by using digital scales, and stature measured by using mecrotoise. The intake of energy, protein, vitamin C, and iron (Fe) were obtained by using the method of recall 2 x 24 hours then calculated using nutrisurvey for windows. Data was analyzed by using chi square test. Results: The result showed that 18,9%  female student was underweight, 52,8% female student had normal weight, 28,3% female student was overweight, and 57,5% respondent was anemia. Based on food consumption was 80,9% lack of energy, 42,5% lack of protein, 86,8% lack of vitamin C, and 86,8% lack of iron (Fe). The result of statistic test showed that there was no relationship between energy intake (p = 0.14), protein (p = 0.33), vitamin C (p = 08) and nutritional status (p = 044) with anemia status. There is a relationship between intake of iron (Fe) (p=0,02) with anemia status. Conclusion: anemia in female students of Muzamzamah-Chosyi`ah may be caused by inadequate intake of iron (Fe) from food..